keefektifan model pembelajaran problem based learning berbantuan audio visual untuk meningkatkan kemampuan kognitif dan kemampuan pemecahan masalah siswa pada energi alternatif - Hana Putri Azzahra; Parlindungan Sinaga; Agus Danawan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The aim of this research is to determine the effectiveness of the problem based learning model assisted by visual audio to improve students' cognitive abilities and problem solving abilities in alternative energy materials. The research method used is a quantitative quasi experimental design method. The population chosen in this research were class XI students at a private high school in the city of Bandung. The sample for this research consisted of 66 students. The sampling technique used was convenienc sampling. The instrument used consisted of 14 questions for cognitive abilities and 21 questions for problem solving abilities. The data analysis technique used to determine cognitive abilities and problem solving abilities uses N-Gain calculations. The results of the research showed that classes that applied the problem based learning model assisted by visual audio had higher increases in cognitive abilities and problem solving abilities compared to classes that only used the problem based learning model. In the experimental class, the N-Gain value for cognitive ability was <g> = 0.84, included in the